Determinants of Electronic Smoking Behavior among Adolescents in Indonesia (Analysis of Global Youth Tobacco Survey 2019) - Hafidah, Farwah; Apriningsih; Simanjorang, Chandrayani; Hanifah, Laily (Public Health of Indonesia, 2024)
Background:E-cigarettes are a concerning issue since e-smoking has affected young people. This phenomenon will be influenced by how common e-cigarette use is among youth. Nevertheless, health experts have found that e-cigarettes have negative effects on health. Objectives:The purpose of this study was to determine factors connected with electronic smoking habits among adolescents in Indonesia. Methods:The 2019 Global Youth Tobacco Survey was used in this cross-sectional study employing a multistage cluster random sampling approach. A total of 7,758 samples were taken after selection based on inclusion criteria. Results:According to this study, 21% of adolescents had tried e-cigarettes. Furthermore, multiple logistic regression analyses revealed that sex (POR: 5.834, 95% CI: 4.749—7.167), allowance (POR: 2.432, 95% CI: 1.874—3.157), obtaining e-cigarette information from friends, shopkeepers, and promotion events (POR: 2.422, 95% CI: 1.959—2.994), and knowledge and attitude (POR: 2.030, 95% CI: 1.683—2.449) were the most influential factors on electronic smoking habits among adolescents in Indonesia. Conclusion:The results indicated that sex, allowance, access to information on e-cigarettes, and the knowledge and attitudes of adolescents strongly influence the likelihood of trying e-cigarettes. Strict policies regarding the use of e-cigarettes among adolescents need to be enforced, especially in regulating advertising and pricing to make them less affordable for adolescents. Keywords:determinants, e-cigarette, smoking, behaviour, adolescent